Primary and secondary structure specificity of the cleavage of 'single-stranded' DNA by endonuclease Hinf I. - Hofer, B (1982)
The interaction of endonuclease Hinf I with single-stranded fd DNA was examined. The sizes of the cleavage products indicate that the enzyme cuts this substrate at the same sequences as double-stranded DNA (GANTC). To determine whether or not the recognition sites in single-stranded DNA have to be present in double-stranded form in order to be cleaved, DNA fragments containing complementary or non-complementary Hinf I sequences were prepared and treated as substrates. The results suggest that completely base-paired recognition sites are necessary for cleavage. Sequences surrounding the Hinf I pentanucleotides significantly modulate the reaction rates.